FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MOTIVASI KERJA PADA RESCUER KANTOR PENCARIAN DAN PERTOLONGAN (SAR) SEMARANG JAWA TENGAH - Widya Saraswati; Ida Wahyuni; Ekawati Ekawati (Jurnal Kesehatan Masyarakat, 2019)
Search and Rescue (SAR) is an activity to find and help people or items that are lost or worried about being lost in a disaster or accident, and Rescuer joined the SAR team. Work motivation is important for Rescuer because motivation can cause, distribute, and support the behavior of workers to be willing, enterprising and enthusiastic in achieving optimal results so that high productivity. This research aims to know the factors related with motivation to work in Rescuer SAR Office. Type of this research is explanatory research using cross sectional approach. Determined of the sample using total sampling is 20 people. The tool used is a questionnire. The survey results revealed that 75% of respondents were highly motivated and 25% had low motivation. Data analysis using Rank Spearman test. Statistical analysis showed that there are correlation between recognition (ρ = 0,001), work it self (ρ = 0,013), the potential development of the individual (ρ = 0,036), perception of salary (ρ = 0,001), working condition (ρ = 0,001), policy and administration (ρ = 0,002), and supervison (ρ = 0,003) with the motivation to work. There was no correlation between responsibility (ρ = 0,151) with the motivation to work.